Iniquidades socioconômicas na saúde bucal de adolescentes - Sfreddo, Camila Silveira (2018)
Socioeconomic inequalities determine a social gradient for the occurrence of oral health in adolescents, and those in lower socioeconomic status present high levels of gingival bleeding and poor oral health-related quality of life (OHRQoL). However, there is an inconsistent evidence of the socioeconomic pathways of inequalities in adolescent’s periodontal health and the longitudinal impact of contextual and individual socioeconomic factors on the OHRQoL of these individuals. The aim of this thesis was to present two papers. The first study explored the pathways by which the socioeconomic inequalities may influence gingival bleeding in adolescents; the second study was to assess the impact of socioeconomic inequalities on OHRQoL over time. This cohort study followed 1,134 Brazilian schoolchildren enrolled in public schools aged 12-years-old for two years. Participants were clinically examined for dental caries, gingival bleeding at six sites per tooth through the Community Periodontal Index, dental biofilm, and malocclusion. The parents answered a semi-structured socioeconomic questionnaire regarding sociodemographic characteristics and use of dental services. Psychosocial variables of subjective happiness were collected through a validated questionnaire. OHRQoL was evaluated through the short Brazilian version of the Child Perceptions Questionnaire for 11- to 14-Year-Old Children (CPQ11-14). Contextual variables related to the school were obtained through official city publications. The data were collected using standardized procedures in the two assessments of the study. The outcomes of this thesis were gingival bleeding at follow-up and OHRQoL over time. Data were analyzed using Structural Equation Models for the first study and Multilevel Linear Regression Models for the second. The neo-materialist pathway through a stronger direct effect of the socioeconomic position explained better inequities in gingival bleeding of adolescents at follow-up. In addition, socioeconomic inequalities through the low income of school’s neighborhood, low family income and low maternal schooling negatively impacted the OHRQoL of adolescents over time. Therefore, the lower socioeconomic status was associated with poor oral health of adolescents. These findings support the need to implement public policies on social determinants in adolescence.